Mango Farmers’ Knowledge and Management of Anthracnose Disease in Rajshahi Division, Bangladesh - Shahriar Hasan; Md. Safiul Islam Afrad; Soumitra Saha; Md. Riazul Islam; Md. Abdul Kader (Journal of Agricultural Extension)
The cultivation of mango is a significant source of revenue in Bangladesh. A survey conducted in 2024 on 240 mango growers identified anthracnose disease as a major concern, affecting fruit quality and causing significant losses, using live specimens and photo tools. Findings indicate that anthracnose was the most common problem in mango cultivation. Approximately 33.8% of those surveyed couldn't name the cause of anthracnose. The majority (85.0%) of respondents employed chemical pesticides against the disease. While pruning infected leaves, twigs, and destroying infected flowers, young fruit was negligible. Only 5.41 percent of them knew the most effective technique, hot water treatment. About 92.5% of respondents solely depend on the pesticide dealer for disease-related solutions, and they were unaware of the protective gear used during pesticide spraying. If the farmers are able to recognize the mango anthracnose disease, understand how the disease spreads, and implement the right management practices, mango farming might become a more profitable endeavor. The study could expand understanding of the farmer and extension staff about mango anthracnose disease and its effective management techniques.